Agroecological Responses of Heavy Metal Pollution with Special Emphasis on Soil Health and Plant Performances - Srivastava, Vaibhav; Sarkar, Abhijit; Singh, Sonu; Singh, Pooja; de Araujo, Ademir S. F.; Singh, Rajeev P. (Frontiers in Environmental Science, 2017)
Following the modern-day urbanization and industrialization, heavy metal contamination has become a prime concern for today’s society. Starting from the agricultural soil in our food basket these heavy metals and metalloids, like - Cr, Mn, Co, Ni, Cu, Zn, Cd, Sn, Hg,Pb and others, showing significant toxic impacts. The intensification of agricultural land-use and changes in farming practices along with technological advancement has led to heavy metal pollution in soil. Metals/ metalloids concentrations in the soil are increasing at alarming rate due to modern day agricultural practices as these could not be degraded and affect plant growth, food safety and soil microflora. The biological and geological reorganization of heavy metal depends chiefly on green plants and their metabolism. Metal toxicity has direct effects and importance to flora that forms the integral component of ecosystem. Altered biochemical, physiological and metabolic processes are found in plants growing in regions of high metal pollution. However, metals like Cu, Mn, Co, Zn and Cr are required in trace amounts by plants for their metabolic activities. The present review aims to catalogue major published works related to heavy metal contamination in modern day agriculture, and draw a possible road map towards future research in this domain.